Proceedings of SPE Eastern Regional Meeting 2004
DOI: 10.2523/91376-ms
|View full text |Cite
|
Sign up to set email alerts
|

Applying Advanced Fracture Diagnostics to Optimize Fracture Stimulation in Coalbed Methane Reservoirs: Case History of Two Fields in the Rocky Mountains

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractCoalbed methane development continues to increase accounting for 8% of U.S. gas production in 2002. Many coalbed methane wells must be stimulated by hydraulic fracturing in order to achieve economic production rates. However, optimizing hydraulic fracture treatments in coalbed methane is difficult and advanced diagnostics can aid in the process. This paper discusses completion optimization for two coalbed methane reservoirs in the Rocky Mountains. Hydraulic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Layered materials have higher resistance to fracturing, and are considered to have a "composite layering effect" to hinder fracture growth (Warpinski et al 1998;Wolhart et al 2004). Some of the mechanisms contributing to a composite-layering effect require interfacial slippage or debonding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Layered materials have higher resistance to fracturing, and are considered to have a "composite layering effect" to hinder fracture growth (Warpinski et al 1998;Wolhart et al 2004). Some of the mechanisms contributing to a composite-layering effect require interfacial slippage or debonding.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that sometimes the fracture is more contained in height than predicted by simulators. Some new mechanisms and explanations have been given, including the "composite layer effect," "shear dampening," and fracture behavior at layer interfaces, for the unexpected height containment (Warpinski et al 1998; Barree and Winterfeld 1998;Wolhart et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…6,11 Some of the mechanisms contributing to a composite layering effect require interfacial slippage or debonding. Layered materials have higher resistance to fracturing, and are considered to have a "composite layering effect" to hinder fracture growth.…”
Section: Discussionmentioning
confidence: 99%
“…6,10,11 On the other hand, more advanced numerical models have been developed for hydraulic fracture simulators, 1,12 and the combined effect of height containment mechanisms can now be studied with fewer approximations for hydraulic fracturing conditions. It has been observed that sometimes the fracture is more contained in height than is predicted by simulators.…”
Section: Introductionmentioning
confidence: 99%